Fat‐suppressed alternating‐SSFP for whole‐brain fMRI using breath‐hold and visual stimulus paradigms. Issue 5 (2nd June 2015) - Jou, Tiffany; Patterson, Steve; Pauly, John M.; Bowen, Chris V.
Abstract : Purpose: To achieve artifact‐suppressed whole‐brain pass‐band‐balanced steady‐state free precession functional MRI from a single functional magnetic resonance imaging (fMRI) scan. Methods: A complete and practical data acquisition sequence for alt‐SSFP fMRI was developed. First, multishot flyback‐echo‐planar imaging (EPI) and echo‐time shifting were used to achieve data acquisition that was robust against eddy currents, gradient delays, and ghosting artifacts. Second, a steady‐state catalyzation scheme was implemented to reduce oscillations in the transient signal when catalyzing in and out of alternate steady states. Next, a short spatial‐spectral radiofrequency (RF) pulse was designed to achieve excellent fat‐suppression while maintaining a repetition time <15 ms to sensitize functional activation toward smaller vessels and capillaries. Lastly, parallel imaging was used to achieve whole‐brain coverage and sufficiently high temporal resolution. Results: Breath‐hold experiments showed excellent fat‐suppression and alt‐SSFP's capability to recover functional sensitivity from signal dropout regions of conventional gradient‐echo and banding artifacts from conventional pass‐band‐balanced steady‐state free precession. Applying fat‐suppression resulted in improved activation maps and increased temporal SNR. Visual stimulus functional studies verify the proposed method's excellent functional sensitivity to neuronal activation. Conclusion: Artifact‐suppressed images are demonstrated, showing a practical pass‐band‐balanced steady‐state free precession fMRI method that permits whole‐brain imaging with excellent blood oxygen level‐dependent sensitivity and fat suppression. Magn Reson Med 75:1978–1988, 2016. © 2015 Wiley Periodicals, Inc.